Anisotropic pinning and the mixed state galvanothermomagnetic properties of superconductors a phenomenological approach - Shklovskij, V. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
In the presence of isotropic and anisotropic pinning the vortex dynamics is discussed in terms of phenomenologically introduced, nonlinear viscosities. The formulas for linear galvanothermomagnetic effects are derived and analyzed under the condition at which the transport current or temperature gradient is directed at arbitrary angle with respect to the unidirected twins, which cause the anisotropic pinning. It is shown that two new effects which appear due to the anisotropic pinning, namely (with respect to the reversal of the magnetic field direction) even transverse and odd longitudinal voltage, have a distinct origin. The first is due to the guided vortex motion, while the second appears only when anisotropic (in contrast with isotropic) pinning changes the Hall drag coefficient. We also show that the last effect might be masked in the experiment by a large, odd contribution, which has the same angular dependence and which appears due to the Ettingshausen effect. In order to clarify the problem of influence of the twins on the Hall drag coefficient, we discuss the possibility of separating these two contributions in the experiment.